2013
DOI: 10.1007/s13277-013-1556-7
|View full text |Cite
|
Sign up to set email alerts
|

Strong expression of cyclin B2 mRNA correlates with a poor prognosis in patients with non-small cell lung cancer

Abstract: Cyclin family proteins act in association with cyclin-dependent kinases (CDK) at cell cycle checkpoints to regulate the eukaryotic cell cycle. CyclinB2 contributes to G2/M transition by activating CDK1 kinase, and cyclin B2 inhibition induces cell cycle arrest. CyclinB2 is overexpressed in various human tumors, though the relationship between cyclin B2 expression and the clinicopathological characteristics of lung cancer and patient prognosis is not well understood. In the present study, therefore, we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…Although the other genes have not yet been deeply studied in glioma, their expression is positively correlated with clinical grade glioma (Table I), which makes them potential therapeutic targets. Moreover, they participate in tumor progression in several cancers, including lung cancer and breast cancer (47)(48)(49)(50)(51)(52). This evidence further confirmed the tumor-promoting role of HOTAIR in glioma and other cancers.…”
Section: Discussionsupporting
confidence: 68%
“…Although the other genes have not yet been deeply studied in glioma, their expression is positively correlated with clinical grade glioma (Table I), which makes them potential therapeutic targets. Moreover, they participate in tumor progression in several cancers, including lung cancer and breast cancer (47)(48)(49)(50)(51)(52). This evidence further confirmed the tumor-promoting role of HOTAIR in glioma and other cancers.…”
Section: Discussionsupporting
confidence: 68%
“…Overexpressed CDK5RAP3 and CCNB2 , as well as suppressed RAGE, may be promising biomarkers in lung adenocarcinoma [33]. The 5-year overall survival rates of LAC patients with low CCNB2 mRNA levels were significantly higher than that with high levels, and overexpressed CCNB2 mRNA can independently predict a poor prognosis in patients with LAC [34, 35]. Immunohistochemical analysis indicates AURKB , which mediates chromosome segregation during mitosis, is frequently overexpressed in primary lung carcinomas [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of CCNB2 has been revealed in cancers such as breast cancer and lung cancer, and it has been reported as a poor prognostic factor [47,48]. In ACC, it is reported that CCNB2 is 5.6-to 14-fold more highly expressed compared with ACA by microarray analysis and that CCNB2 is overexpressed in more aggressive forms of ACC [35,49,50,51].…”
Section: Plos Onementioning
confidence: 99%